Overcoming human barrier as a measure towards improved knowledge management - Marican, Sabitha; Abdullah, Siti Alida John (IBIMA Publishing, 2008)
Knowledge management involves delivering of information to a person or a set of people, which necessitates two or more people communicating directly face to face, indirectly or in a virtual environment. Human barrier in this paper refers to sexual harassment behaviors that are unwanted and unwelcome that occurs in the form of verbal, non verbal, physical and visual actions among workers at workplace.It acts a as communication barrier to knowledge sharing, which works best when the people who generate and exchange knowledge, maintain good relation among workers. In this paper, the findings on sexual harassment perception, experience and complain mechanisms based on quantitative and qualitative study among Malaysian public sector administrators will be discussed in relation to the worker relationship that is needed for the exchange of knowledge in the organization.Finally the paper outlines strategies to overcome sexual harassment at workplace, as knowledge is of little use unless it is distributed, mediated and shared for the benefited of the organization.